2018
DOI: 10.1111/nicc.12403
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and experiences of relatives of patients discharged home after critical illness: a systematic integrative review

Abstract: Background Patients discharged from intensive care may experience psychological and physical deficits resulting in a long and complex rehabilitation upon discharge. Relatives are also vulnerable to psychological pathologies and diminished health‐related quality of life following the patients' critical illness. Relatives often provide care during the patients' rehabilitation, which may influence their health. Aim To report the outcomes and experiences of relatives of patients discharged home after critical illn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…The majority of patients who survive a critical illness require significant help with activities of daily living and depend on family caregivers for support. While family caregivers have identified positive aspects of their ICU caregiving experience (Tate & Choi, 2020), they are often unprepared to assume burdensome caregiving responsibilities after the patient returns home (Choi et al, 2018; Levine & Reinhard, 2016; Stayt & Venes, 2019). Ongoing caregiving responsibilities can have persistent negative effects on caregivers’ quality of life (Cameron et al, 2016; Choi et al, 2011; Douglas & Daly, 2003; Hickman & Douglas, 2010).…”
Section: Family Caregiver Participation In Patient Care In the Icumentioning
confidence: 99%
“…The majority of patients who survive a critical illness require significant help with activities of daily living and depend on family caregivers for support. While family caregivers have identified positive aspects of their ICU caregiving experience (Tate & Choi, 2020), they are often unprepared to assume burdensome caregiving responsibilities after the patient returns home (Choi et al, 2018; Levine & Reinhard, 2016; Stayt & Venes, 2019). Ongoing caregiving responsibilities can have persistent negative effects on caregivers’ quality of life (Cameron et al, 2016; Choi et al, 2011; Douglas & Daly, 2003; Hickman & Douglas, 2010).…”
Section: Family Caregiver Participation In Patient Care In the Icumentioning
confidence: 99%
“…Previous studies have found that when pleasantness was perceived as high, the environment was also perceived as safe, secure, and stimulating (Bengtsson & Carlsson, 2006;Shih & Ramilo, 2014). Previous research has reported that families of critically ill patients cared for in ICUs experience serious types of ill-being such as depression, anxiety, and fatigue (Apple, 2014;Celik et al, 2016;Day et al, 2013); sometimes, they even develop post-traumatic stress disorder (Petrinec & Daly, 2016;Stayt & Venes, 2019;Wintermann et al, 2016). These findings from the refurbished intervention room can be a way of reducing some elements of ill-being.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy family function may be facilitated by health professionals supporting the family during the ICU stay while following proper guidelines . There is a need to design strategies to support families throughout all stages of critical illness . The intervention does not exclude individual support for the family members.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 There is a need to design strategies to support families throughout all stages of critical illness. 33…”
Section: Discussionmentioning
confidence: 99%